A systematic review investigating the relationship between efficacy and stimulation parameters when using transcutaneous electrical nerve stimulation after knee arthroplasty - Beckwée, David (SAGE Open Med, 2014)
OBJECTIVE: To evaluate the clinical efficacy of transcutaneous electric nerve stimulation in the treatment of postoperative knee arthroplasty pain and to relate these results to the stimulation parameters used. DATA SOURCES: PubMed, Pedro and Web of Knowledge were systematically screened for studies investigating effects of transcutaneous electric nerve stimulation on postoperative knee arthroplasty pain. REVIEW METHODS: Studies were screened for their methodological and therapeutical quality. We appraised the influence of the stimulation settings used and indicated whether or not a neurophysiological and/or mechanistic rationale was given for these stimulation settings. RESULTS: A total of 5 articles met the inclusion criteria. In total, 347 patients were investigated. The number of patients who received some form of transcutaneous electric nerve stimulation was 117, and 54 patients received sham transcutaneous electric nerve stimulation. Pain was the primary outcome in all studies. The stimulation settings used in the studies (n = 2) that reported significant effects differed from the others as they implemented a submaximal stimulation intensity. Stimulation parameters were heterogeneous, and only one study provided a rationale for them. CONCLUSION: This review reveals that an effect of transcutaneous electric nerve stimulation might have been missed due to low methodological and therapeutical quality. Justifying the choice of transcutaneous electric nerve stimulation parameters may improve therapeutical quality.